Copper-catalyzed radical ring-opening halogenation with HX. Issue 69 (10th August 2021) - Liu, Shuai; Bai, Ming; Xu, Peng-Fei; Sun, Qing-Xin; Duan, Xin-Hua; Guo, Li-Na
Abstract : An efficient copper-catalyzed radical ring-opening halogenation with HX (aq) is described. This protocol provides a practical access to distally chlorinated, brominated and iodinated alkyl ketones and alkyl nitriles with moderate to good yields. Abstract : An efficient copper-catalyzed radical ring-opening halogenation with HX (aq) is described. This protocol features redox-neutral conditions, green halogen sources, and a broad substrate scope, providing practical access to distally chlorinated, brominated and iodinated alkyl ketones and alkyl nitriles with moderate to good yields.